Disrobing and redressing sex - Guevara, Geoffrey (2013)
This research is a precursor to further studies on socio-cultural issues such as reproductive health, homosexual marriages, infidelity and teen- age sexuality. With the goal of creating a framework for a resolution to these issues, the author focuses on sex as the central question. Prog- ress in debates on these issues and the general ethos depend on peo- ple’s attitude towards sex. In the Philippines, sex unfortunately remains in the cloister of morality and marital obligations, despite changes in time and social needs. Though the virtues of chastity and fidelity remain important, this author suggests a frame outside morality and Christian duty through which sex can be appreciated. The author uses the lenses of philosophy, particularly Max Scheler’s non-formal ethics of values, with supporting insights from the development psychologist, Evelyn Eaton Whitehead and her husband, James, a pastoral theologian, to reframe how sex is viewed. The author’s thesis is that sex is good and, when done properly, can be a vehicle for human persons to touch the fundamentals of their finitude and the glory of their existence.
Keywords: Human sexuality; Human beings -- Philosophy